PERSPECTIVES AND CHALLENGES FOR SOCIAL ENTREPRENEURSHIP DEVELOPMENT IN UKRAINE - M. Naumova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The assessment of the current state and prospects of social entrepreneurship development in Ukraine based on qualitative and quantitative SWOT analysis, taking into account the synergy between the opportunities and threats, strengths and weaknesses of the object are suggested and conducted in the article. The expert survey method was applied to evaluate the factors are identified through SWOT analysis.The priority areas of social entrepreneurship development in Ukraine had been identified on the basis of the sophisticated matrix of the SWOT- analysis. The overriding objectives of social entrepreneurship development in Ukraine are making public authorities as well as civil society aware of the solutions required for the problems of social entrepreneurship development in Ukraine through media and communications.The adoption of the Act on social entrepreneurship and its support at the national, regional and local level; the formulation and adoption of the special long-term development programmes to promote social entrepreneurship, introduce legislation to set up a specific registration system for social enterprises, including the regularly monitoring of their activities - the measures are necessary to achieve more effective implementation and increasing the scope and scale of social entrepreneurship in Ukraine.The establishment of the education programmes in the field of social entrepreneurship in the universities, organizing and conduction of teaching workshops, trainings, and courses on social entrepreneurship for the wide public - would give new impetus to the development of social entrepreneurship in Ukraine as the source of the citizens' initiatives.